The effects of disability on households' economic livelihoods and poverty in Vietnam - Sean Kiely; Dorothee Buehler; Ute Rink; Kristin Kiesel (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2023)
Could households be both more vulnerable and more resilient to shocks depending on the type of shock experienced and the overall circumstances in which they live? If so, what policy implications can be drawn from such findings? We investigate both the immediate effects of shocks on household's income and assets, and the longer-term poverty dynamics of households with a disabled member (DH) and without a disabled member (NDH) in Vietnam. Additionally, we assess differences in behaviors and beliefs between these two household groups and the extent to which these differences can explain variations in the impact of shocks on their economic livelihoods. Our results indicate that DHs are more risk averse and believe they will face more health shocks than NDHs, but also experience a greater number of health shocks and total shocks. Examining the immediate impact of shocks, we find that DHs are more resilient in the face of health-related shocks, however, they face large income losses when confronted with weather and agricultural shocks. While these immediate effects may lead one to conclude that policies for DHs should address these natural shocks, our poverty dynamics analysis paints a different picture. Households with a disabled member that face one or more health shocks are significantly more likely to have experienced chronic or transitory poverty than households where a disability is not present. Yet, these households are no more likely to end up in poverty when faced with shocks outside of the health domain. This suggests that the greater number of cumulative shocks, primarily driven by more frequently experienced health shocks, makes them more vulnerable to natural shocks than NDHs and weakens their overall resiliency. Thus, the cumulative number of health shocks may be the strongest determinant of poverty in the long run for DHs, and policies aimed at reducing poverty need to account for the unique experiences of these households.
Keywords: D13; I32; I12; 330; Poverty dynamics; Disability; Cumulative shocks; Risk preferences; Panel data; Vietnam